Penerapan Model Make A Match Untuk Meningkatkan Hasil Belajar Pai Materi Asmaul Husna Siswa Kelas IV - Muhamad Rif'an; Rohma Yunita; Imam Fauzi (Najah Bestari, 2026)
This study was motivated by the low learning outcomes in Islamic Religious Education (PAI) on the topic of Asmaul Husna among fourth-grade students of SDN 13 Way Khilau, which was caused by teacher-centered learning. This study aims to improve learning outcomes in PAI on the topic of Asmaul Husna through the application of the Make a Match learning model. This research is a Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection. The subjects were 25 fourth-grade students. Data were collected through tests, observation, and documentation, then analyzed using quantitative and qualitative descriptive techniques. The results show an increase in classical completeness from 40% in the pre-cycle to 64% in cycle I and 88% in cycle II, accompanied by an increase in student activeness. Thus, the application of the Make a Match model can improve PAI learning outcomes on Asmaul Husna for fourth-grade students of SDN 13 Way Khilau.